Longitudinal motion control for high-speed trimaran based on computational fluid dynamics and predictive control. (22nd June 2020) - Liu, Zhilin; Zheng, Linhe; Li, Guosheng
This article investigates a model predictive control (MPC) with disturbance observer (DOB) for a trimaran longitudinal motion control. Firstly, to design the trimaran longitudinal motion stability controller, the mathematical model of the trimaran requires to be obtained. The hydrodynamic coefficients in the mathematical model are obtained by the computational fluid dynamics simulation. Secondly, a T-foil with the fixed attack angle is selected as an antipitching appendage. It is verified that the T-foil is effective in restraining the longitudinal motion of the trimaran through numerical simulation. Lastly, to enhance the ability of the T-foil for restraining the severe longitudinal motion, a controller based on the MPC method with DOB is designed to control the attack angle. The effect of the proposed algorithm is verified by theoretical analysis and simulation.